Analisis kinerja turbin gas (GT 3.1) PLTGU Muarakarang setelah masa konstruksi sesuai ISO 2314:2009 - Wibowo, Budi Ari (Journal of New Energies and Manufacturing, 2022)
PLN has determined the construction of the Muarakarang CCPP to balance the growth demand for electricity, which began in 2017 and has entered the testing phase in early 2020. Muarakarang CCPP uses gas turbines M701F5 manufactured by Mitsubishi Hitachi Power System with a net GT output of 341.300 kW, efficiency of 41.9% and a Net Plant Heat Rate of 2129 kCal/kWh. The problem is that due to differences in environmental conditions between the manufacturer and the project site, the delivery and transportation process as well as the assembly at the project site, there will be a deviation in the conditions of the operating parameters that cause changes in the performance of the gas turbine. So it is necessary to test the performance of the gas turbine after it is installed with quantitative and comparative research methods referring to the ISO standard: 2314 Gas Turbine Acceptance Test, which is to take the operating data directly at the same time and perform calculations with the input and output methods. The test results and calculations show that the net gt output is 345,721 kW, which is 4,421 kW higher than the manufacturer’s design and performance guarantee, NPHR is obtained at 2,099.7 kcal/kWh, which is lower or more efficient by 29.3 kcal/kwh from the manufacturer’s design and performance guarantee and the resulting efficiency is 41.9%, 1.6% higher than the manufacturer’s design. This means that this gas turbine has met the performance guarantee and there is no damage during the delivery and installation process and the results of this calculation can be used as a reference for the next turbine performance evaluation.